Hands-on cloud-native microservices with Jakarta EE : build scalable and reactive microservices with Docker, Kubernetes, and OpenShift /: build scalable and reactive microservices with Docker, Kubernetes, and OpenShift. ([2019]) - Fugaro, Luigi; Vocale, Mauro
No abstract available